Universal model of computer network on basis technologists of bluetooth - Дудник, A. C.; Варганич, М. В.; Гладыш, И. А. (Problems of Informatization and Control, 2008)
An universal model is built for the networks of bluetooth, taking into account parameters and terms of work of the real network. The version of one of the universal widely spoken imitation simulation languages is used